Highly Cytotoxic Molybdenocenes with Strong Metabolic Effects Inhibit Tumour Growth in Mice. Issue 4 (29th November 2022) - Fuchs, Valentin; Cseh, Klaudia; Hejl, Michaela; Vician, Petra; Neuditschko, Benjamin; Meier‐Menches, Samuel M.; Janker, Lukas; Bileck, Andrea; Gajic, Natalie; Kronberger, Julia; Schaier, Martin; Neumayer, Sophie; et al.
Abstract: A series of six highly lipophilic Cp‐substituted molybdenocenes bearing different bioactive chelating ligands was synthesized and characterized by NMR spectroscopy, mass spectrometry and X‐ray crystallography. In vitro experiments showed a greatly increased cytotoxic potency when compared to the non‐Cp‐substituted counterparts. In vivo experiments performed with the dichlorido precursor, (Ph2 C−Cp)2 MoCl2 and the in vitro most active complex, containing the thioflavone ligand, showed an inhibition of tumour growth. Proteomic studies on the same two compounds demonstrated a significant regulation of tubulin‐associated and mitochondrial inner membrane proteins for both compounds and a strong metabolic effect of the thioflavone containing complex. Abstract : A series of molybdenocenes containing lipophilic substituted Cp ligands as well as bioactive chelating ligands have shown cytotoxicity against lung, colon and ovarian cancer in vitro; one complex showed the greatest anticancer activity of any Mo‐based agent known to date. Significant tumour growth inhibition was observed in in vivo studies while proteomics showed the most active compound had a strong effect on cellular metabolic processes.